(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This paper delves into cloud computing, a transformative technology reshaping data management, storage, and IT services. The study explores the fundamentals, growth, and impact of cloud computing, addressing its advantages and challenges, with a focus on security, scalability, and cost-efficiency. Through a comprehensive literature review, this research investigates existing studies, methods, and findings on cloud adoption across industries. The paper analyses data from industry reports and surveys, providing insights into cloud adoption trends and user experiences. The conclusion underscores the potential and challenges of cloud computing, suggesting directions for future research.